2002
DOI: 10.1007/s00425-002-0868-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and formation of indole-3-acetamide in Arabidopsis thaliana

Abstract: An HPLC/GC-MS/MS technique (high-pressure liquid chromatography in combination with gas chromatography-tandem mass spectrometry) has been worked out to analyze indole-3-acetamide (IAM) with very high sensitivity, using isotopically labelled IAM as an internal standard. Using this technique, the occurrence of IAM in sterile-grown Arabidopsis thaliana (L.) Heynh. was demonstrated unequivocally. In comparison, plants grown under non-sterile conditions in soil in a greenhouse showed approximately 50% higher averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 27 publications
4
89
0
1
Order By: Relevance
“…1). This expression pattern nicely reflects the kinetic of IAA during the first two weeks of seedling development, 9 and the rapid growth of seedlings during that time. Seeds usually contain high levels of stored IAA, which facilitates initial seedling growth.…”
Section: Ami1 Expression Is Presumably Suppressed By Lec1mentioning
confidence: 56%
“…1). This expression pattern nicely reflects the kinetic of IAA during the first two weeks of seedling development, 9 and the rapid growth of seedlings during that time. Seeds usually contain high levels of stored IAA, which facilitates initial seedling growth.…”
Section: Ami1 Expression Is Presumably Suppressed By Lec1mentioning
confidence: 56%
“…Arabidopsis nitrilases (NIT1, NIT2, and NIT3) can convert IAN to IAA and IAM in vitro (25). Since our results indicated that IAN is mainly produced from IAOx, we hypothesized that IAM is a possible intermediate in the pathway converting IAOx to IAA (Fig.…”
Section: Ian Ig and CL Are Each Produced Independently From Iaox Inmentioning
confidence: 77%
“…Arabidopsis nitrilases (NIT1, NIT2, and NIT3) convert IAN to IAA and indole-3-acetamide (IAM) (Pollmann et al, 2002). IAA is an auxin and some microarrays analyses have demonstrated up-regulation of NIT1 and NIT2 in response to IAN and NaCl treatment (Grsic et al, 1998;Jiang et al, 2007;Woodward and Bartel, 2005).…”
Section: Ataf2 Is Required For Full Induction Of Nit2 In Arabidopsismentioning
confidence: 99%